Soviet Budgets after Stalin - Nove, A. (The Review of Economics and Statistics, 1954)
THERE have now been two post-Stalin budgets, which in structure and presentation differ so appreciably from their predecessors as to cause acute confusion in the minds of many commentators. The differences have not been explicitly stated in Soviet sources, but can be deduced from them, though the evidence is insufficient for an arithmetically precise account of what has occurred. The objects of the present paper are, first, to examine the budgets for the light they shed on the development of the Soviet economy in the last two years, and, second, to explain as far as possible the changes since Stalin's death in the structure of the budget itself. Obviously, these two aims overlap, since a change in the definition of a budgetary heading affects any conclusions one can draw about or from its magnitude. The I953, and still more the I954, budget sessions of the Supreme Soviet are simultaneously informative and acutely frustrating; there is a substantial volume of new data, but some information is missing, and comparison with previous years is rendered difficult by complex and inadequately explained changes in structure and definition. One new feature is that the Soviet leaders have spoken in the budget debates and in the course of their speeches have given useful economic, political, and information. Under Stalin, the speech of the unchanging Minister of Finance, Zverev, was followed by routine speeches of little interest by persons of medium or lowly rank, while the top party leadership remained in the special seats reserved for them on the platform and said nothing. Malenkov broke with precedent when he addressed the I953 budget session; he spoke again in I954, as did such major personalities as Khrushchev, Kaganovich, and Mikoyan. Since men of this stature, whose speeches were to be reprinted in millions of copies, could not confine themselves merely to repeating the points already made by the relatively less important Zverev, this in itself ensured that the session would be more informative than had been the case under Stalin. Unfortunately, the increasing political importance of the budget session has led to a noticeable decline in what might perhaps be called statistical integrity; before I953, while certain data were from time to time suppressed, the budget figures always appeared to be reasonably reliable; it will be shown that in I953-54 there has been a marked increase in propaganda-statistics. Table i compares the results of the I952 budget, the last of the Stalin era, with the original estimates and provisional results for I953, and with the estimates for I954. Unfortunately, a complete set of comparable figures for all items cannot be reconstructed from official sources, and in certain cases it has been necessary to make deductions from indirect data, of varying degrees of accuracy; these are explained in the notes to the table. One is immediately struck by the very large increase in the unspecified items of both revenue and expenditure from their I952 levels. This reflects the changes in presentation to which reference has already been made; the analysis of the details of these changes will be left to one side for the present, though it must be stressed that they are of quite vital importance to a proper understanding of the budget as a whole. Revenue from turnover tax shows a downward trend, although both the production of taxable commodities and retail trade turnover are rapidly rising. The volume of turnover of state and cooperative trade in I953 was stated to be 2I per cent above that of I952; it is planned to rise by I5 per cent in I954 and reach a level 75 per cent above that of I950. The fall in turnover tax yield is, of course, due to the cuts in retail prices and increases in prices paid by the state to agricultural producers. The I954 estimated yield is below that of I950. Retail prices, according to Mikoyan, are only 25 per cent below I950 levels. In comparing the relative changes in trade turnover and prices, some commentators find it hard to see why turnover tax revenue should be fall-